Laminar, transitional and turbulent annular flow of drag-reducing polymer solutions - Japper-Jaafar, Azuraien; Escudier, Marcel; Poole, Robert (Elsevier, 2010)
Mean and rms axial velocity-profile data obtained using laser Doppler anemometry are presented together with pressure-drop data for the flow through a concentric annulus (radius ratio 0.506) of a Newtonian (a glycerine-water mixture) and non-Newtonian fluids - a semi-rigid shear-thinning polymer (a xanthan gum) and a polymer known to exhibit a yield stress (carbopol). A wider range of Reynolds numbers for the transitional flow regime is observed for the more shear-thinning fluids. In marked contrast to the Newtonian fluid, the higher shear stress on the inner wall compared to the outer wall does not lead to earlier transition for the non-Newtonian fluids where more turbulent activity is observed in the outer wall region. The mean axial velocity profiles show a slight shift (~5%) of the location of the maximum velocity towards the outer pipe wall within the transitional regime only for the Newtonian fluid.